Doping disorder and the reduction–doping process in LiSrPO4. Issue 40 (6th October 2017) - Santos, Ricardo D. S.; Rezende, Marcos V. dos S.
Abstract : A systematic theoretical study was performed on trivalent and divalent rare-earth (RE) dopant ions in the LiSrPO4 structure, using atomistic simulations based on lattice energy minimization. Abstract : A systematic theoretical study was performed on trivalent and divalent rare-earth (RE) dopant ions in the LiSrPO4 structure, using atomistic simulations based on lattice energy minimization. It was found that RE 3+ and RE 2+ ions are most energetically favorable for incorporation at the Sr site. For RE 3+ ion incorporation, charge compensation by vacancies or anti-site defects are both probable. In order to investigate the reduction–doping process (Europium reduction), two schemes (open atmosphere and H2 reducing atmosphere) were considered. A H2 reduction atmosphere was found to be the most effective agent for Eu reduction. Results reveal that the most probable charge compensation mechanism and the host site preference for rare-earth doping ions play important roles in the investigation of the mechanism of the luminescence properties of LiSrPO4 .